Problematika Penerapan Metode Yanbu’a di Pondok Pesantren Tanwirul Qulub Sungelebak Karanggeneng Lamongan (Al-Tarbiyah : Jurnal Ilmu Pendidikan Islam, 2026)
This study discusses the implementation of the Yanbu'a Method at Pondok Pesantren Tanwirul Qulub. The education sector today faces various changes influenced by the rapid advancement of knowledge, technology, and the impact of globalization, which also affects religious education, particularly in the teaching of the Qur'an. One of the main obstacles in Qur'anic teaching is the use of methods that do not align with the tajwid or makhorijul huruf as taught by Prophet Muhammad SAW. This can lead to critical errors in reading the Qur'an. Therefore, this study aims to explore the challenges that arise in the process of teaching the Qur'an using the Yanbu'a Method at Pondok Pesantren Tanwirul Qulub, which is applied by KH. Agus Musta'in Ilyas. This research uses a qualitative approach based on Max Weber's Verstehen theory. The results show that the obstacles in implementing the Yanbu'a Method include a lack of coordination among teachers, significant differences in students' abilities, low student discipline in muroja'ah, and students' activities outside Qur'anic learning hours. To optimize the implementation of this method, it is recommended to provide teacher training and workshops, group students based on their abilities, strengthen evaluation and monitoring, establish consistent learning schedules, and increase student motivation.